Tolerance of chia seeds to copper - Raquel Stefanello; Patrícia Carine Hüller Goergen; Carmine Aparecida Lenz Hister; Ubirajara Russi Nunes (Acta Biológica Catarinense, 2018)
Environmental contamination by toxic metals has become a problem for plants, animals and man. Among the toxic metals present in the environment, copper (Cu) is the most important contaminant and can, when excess in water or soil, cause disturbances in the growth and development of plants, reducing the productivity of crops. The objective of this study was to evaluate the tolerance of chia seeds to copper during germination. The seeds were placed on paper soaked in aqueous copper solution at concentrations corresponding to zero (distilled water); 60; 120; 180 and 240 mg L-1. The evaluated parameters were: percentage of germination, first count, total length, shoot and root length and dry mass of seedlings. The increase of copper concentration in the substrate promoted a significant decrease in seed germination, growth and dry mass of chia seedlings. It is concluded that chia seeds moderately tolerate exposure to copper at concentrations of up to 120 mg L-1 of Cu in the germination phase and up to 60 mg L-1 in the initial development phase.